The influence of work context and organizational well-being on psychophysical health of healthcare providers - Zaghini, Francesco; Vellone, Ercole; Maurici, Massimo; Sestili, Cristina; Mannocci, Alice; Ercoli, Elisa; Magnavita, Nicola; La Torre, Giuseppe; Alvaro, Rosaria; Sili, Alessandro (La Medicina del Lavoro, 2020)
Background: A high level of organizational well-being improves employee performance and influences the physical and mental health of healthcare providers and students. Objective: This study investigates the relationship between the work context, organizational well-being, and the psychophysical health of healthcare providers. Methods: A multicentre cross-sectional descriptive study was conducted on a sample of healthcare providers (physicians and nurses) and healthcare students (medical students and nursing students). A self-report questionnaire was administered between September and November 2016. Results: Of the 300 questionnaires administered, 201 (67%) were correctly completed. Overall, both the physical and mental health of the healthcare providers and students are explained by the variables of the organizational context: organizational well-being and socio-demographic/work characteristics. In particular, the results show a dependence on gender and age. Furthermore, decision latitude had a positive effect on physical health (b=.134) while job demands had a negative effect (b=-.160) explaining 21% of the PCS of the healthcare providers and students (R2=.209). Mental health improved via the satisfaction (b=.345), and positivity (b=.222) of healthcare professionals and students of these disciplines. Discussion: The results are significant because they directly impact the quality of care provided as well as patient safety.